THE IDEO-ARTISTIC SELF-IMAGE OF LOVE LYRICS A. A. AKHMATOVA (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, we have examined the love lyrics of A. A. Akhmatova. The article analyzes one of the poems by A. Akhmatova.